Die Kommune als wahrer „Lernort“ – eine neue Perspektive für Bildungsregionen? Zum besonderen Ergänzungsverhältnis bedeutsamer Lernorte: Schule und Kommune - Asselmeyer, Herbert (International Dialogues on Education Journal, 2017)
This contribution deals with the explication of the idea and concept of learning regions, to which school networks make an important contribution, because they are the only type of organization with compulsory enrolment. Learning regions can be a network of potenial individual pedagogical institutions, in order to help discover and expand gifts and talents even more effectively. Communes are „the true learning places, for children and adults. Here the young person learns what matters in life, how to configure one’s life with others and to assume responsibility“ (Hüther, 2013).